A novel transformerless high step‐Up DC‐DC converter with active switched‐inductor and quasi‐Z‐source network. Issue 9 (12th May 2021) - Zhao, Jiawei; Chen, Daolian; Jiang, Jiahui
Abstract: Conventional dc–dc boost converters have limited boosting capabilities, and the main switching device may suffer relatively high voltage stress and current stress. A novel transformerless dc‐dc boost converter is proposed in this paper. The proposed topology, which combines the traditional active switch‐inductor and quasi‐Z‐source network, can increase the voltage gain without limiting the duty cycle or increasing the voltage and current stresses of the power switches. The detailed analysis including working principles, steady‐state characteristics, non‐ideal element analysis and a comprehensive comparison is also presented in this paper. To verify the proposed converter's performance, a prototype circuit with 20–30 V input voltage, 200 V output voltage, and 200 W output power is implemented in the laboratory. Experiment results confirm the theoretical analysis and advantages of the proposed converter.